O ENSINO DE ARTE NA EDUCAÇÃO INCLUSIVA: Uma análise de mediação pedagógica. - Maria Aparecida Miatello (2024)
This research aims to analyze pedagogical mediation in art education, focusing on the perspective of inclusive education, based on empirical evidence from pedagogical practice developed from a didactic sequence applied to students in Elementary School I. To achieve this purpose, a qualitative research was conducted in two public schools in the city of Nova Andradina, located in the interior of the state of Mato Grosso do Sul, where the researcher works as a teacher in the Municipal Education Network. The study focuses especially on education as a space for methodological procedures, encompassing literature reviews of theorists and legislation related to pedagogical mediation and inclusive education, in addition to the application of a didactic sequence in two classes of the initial grades of Elementary School I. The works of Vygotsky (2001, 2021), Fernandes (2016) and Saviani (2019), among others, are important theoretical references for this study. The collection of information was carried out through descriptions of pedagogical practices, which formed the basis for the considerations and conclusions of the research. The main results indicated that art teaching promoted an experience of learning, creation and meaningful inclusion. Finally, we hope that this research will contribute to the improvement of studies on inclusion and art teaching.